EFFECT OF VERMICOMPOST FERTILIZER DOSAGE WITH OR WITHOUT FERMENTATION OF Effective Microorganism-4 (EM4) ON GROWTH AND PRODUCTION OF DWARF ELEPHANT GRASS (Pennisetum purpureum cv. Mott) - J. A., Sirait; Budiasa, I K. M.; Trisnadewi, A. A. A. S. (Jurnal Peternakan Tropika; Vol 12 No 1 (2024): Vol. 12 No. 1 Tahun 2024; January - February, 2024)
This research was conducted to find out the growth and yield of kate elephant grass (Pennisetum purpureum cv. Mott) given vermicompost fertilizer dosage with or without Effective Microorganism-4 (EM4) fermentation at different doses. The research was conducted at the Greenhouse, Sesetan Research Station, Faculty of Animal Husbandry, Udayana University on Jalan Raya Sesetan Gang Markisa. The study lasted for 8 weeks, using a completely randomized design (CRD) with eight treatments and four replications so there were 32 experimental units. The treatment given was a dose of vermicompost fertilizer (K) and fermented vermicompost fertilizer Effective Microorganism-4 (EM4) (KF), consisting of K5 : 5 tons ha-1, KF5 : 5 tons ha-1, K10 : 10 tons ha-1 , KF10 : 10 tons ha-1, K15 : 15 tons ha-1, KF15 : 15 tons ha-1, K20 : 20 tons ha-1, KF20 : 20 tons ha-1. The variables observed were growth, yield, and growth characteristics. The growth variable showed significant differences in plant height and was highest in KF20 at a dose of 20 tons ha-1. The number of leaves and tillers showed no significant different results. The yield variable showed no significant difference in dry weight of leaves, dry weight of stems, dry weight of roots, and total dry weight of forage. Growth characteristics showed no significant differences in the ratio of dry weight of leaves to dry weight of stems, the ratio of total dry weight of forage to dry weight of roots, and leaf area per pot. It can be concluded that the application of vermicompost fertilizer without and with Effective Microorganism-4 (EM4) fermentation has not produced real growth and yields. A dose of 20 tons ha-1 with Effective Microorganism-4 (EM4) fermentation is the best dose to increase the height of kate elephant grass (Pennisetum purpureum cv. Mott).